2017
DOI: 10.1016/j.jmoldx.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Collection Tubes from Three Different Manufacturers for the Collection of Cell-Free DNA for Liquid Biopsy Mutation Testing

Abstract: The improvement in sensitive techniques has allowed the detection of tumor-specific aberrations in circulating tumor (ct) DNA. Amplification-refractory mutation system PCR has been used for the analysis of ctDNA to detect resistance-causing mutations in the epidermal growth factor receptor gene (eg, EGFR T790M) in lung cancer patients. So far, Streck tubes have been widely used as standard blood collection tubes. Here, we compared blood collection tubes manufactured by Streck with tubes from Roche and Qiagen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 8 publications
1
40
0
1
Order By: Relevance
“…In 2010, when patient recruitment started for the OncoTrack research project, the knowledge about stabilizing ctDNA in plasma samples was not as advanced as it is today. Most publications regarding the superior effect of EDTA and other blood collection tubes on preserving cfDNA and CTCs, while preventing hematopoietic cells from lysis, were published since 2016 . In 2004, Lam et al reported that EDTA is a superior anticoagulant compared to heparin, but only when blood processing was delayed, whereas comparable results regarding DNA concentrations were obtained when plasma was isolated within 6 hours after blood draw .…”
Section: Methodsmentioning
confidence: 99%
“…In 2010, when patient recruitment started for the OncoTrack research project, the knowledge about stabilizing ctDNA in plasma samples was not as advanced as it is today. Most publications regarding the superior effect of EDTA and other blood collection tubes on preserving cfDNA and CTCs, while preventing hematopoietic cells from lysis, were published since 2016 . In 2004, Lam et al reported that EDTA is a superior anticoagulant compared to heparin, but only when blood processing was delayed, whereas comparable results regarding DNA concentrations were obtained when plasma was isolated within 6 hours after blood draw .…”
Section: Methodsmentioning
confidence: 99%
“…For blood storage until analysis, the choice between commonly available EDTA tubes and cell stabilizing tubes should depend on the transportation time: for in‐house samples processed within 4–6 hours after collection, EDTA tubes are sufficient to extract cfDNA. 62–64 Longer periods of storage or transportation warrant the use of tubes containing cell‐stabilizing reagents . From these tubes, steady cfDNA quality can be obtained after up to 1 week of storage, independent of the temperatures tested in the analysis (4°C or room temperature) .…”
Section: Cfdna Extraction From Blood and Other Materialsmentioning
confidence: 99%
“…62 use of tubes containing cell-stabilizing reagents. [65][66][67][68][69][70] From these tubes, steady cfDNA quality can be obtained after up to 1 week of storage, independent of the temperatures tested in the analysis (48C or room temperature). 71 Although manufacturers claim that cfDNA and cells are stable within the cell stabilizing tubes for 2 weeks, 1 study reported an increase of high molecular DNA after 7 days of storage at 48C and room temperature.…”
Section: Cf D Na E Xtr Ac Ti On Fr Om Bl Ood a Nd Oth E R M A Te Rimentioning
confidence: 99%
“…If specimen processing can be performed within 6 h from collection, standard K2EDTA collection tubes are suitable for blood sampling. However, when the processing is delayed by up to 48 h, specialized cell-stabilizing blood collection tubes should be used to reduce contamination by genomic DNA released from leukocyte lysis (Alidousty et al, 2017;Medina Diaz et al, 2016;Merker et al, 2018;Risberg et al, 2018;Ward Gahlawat et al, 2019;Warton et al, 2017). Current evidence recommends that isolated plasma, not whole blood, can be stored frozen up to 9 months or up to a few years, depending on analytical goals (van Dessel et al, 2017;Meddeb et al, 2019).…”
Section: Current Technologies In Ctdnamentioning
confidence: 99%